Academic Mobility for Engineering and Technology Graduates in Africa: Lessons and Experiences from the Implementation - N, Banadda; E, Dintwa; I. N, Oteyo; P, Nampala; L, Vandepitte; E, Adipala (International Journal of Sustainable Development & World Policy, 2017)
This paper was inspired by lessons and experiences arising from the implementation of an on-going academic mobility project supported by the Intra-ACP European Commission Program. Twelve universities (11 in Africa and the University of Gent in Belgium, Europe) in a consortium brokered by the Regional Universities Forum for Capacity Building in Africa (RUFORUM) conceived and successfully put a proposal in response to the 2013 Intra-ACP Academic Mobility Call. The project “Mobility for Engineering and Technology Graduates in Africa (METEGA)” is on-going and entails academic mobility of 72 beneficiaries (44 at Masters level, 20 at Doctoral level, and 8 at the staff and faculty level) in sixteen countries of the five sub-regions in Africa. Africa is lagging behind in terms of numbers of graduate students in engineering fields. The METEGA project is one of the 15 partnerships on academic mobility supported by the EU Intra-ACP Academic Mobility Scheme; and constitutes significant a contribution towards increasing the number of graduate students in Africa. The project has provided opportunity to leverage resources among participating universities. The participating universities offered three and nine quality Doctoral and Masters training programs. This project represents a significant effort towards internationalization of higher education in the sciences and has served as an opportunity for graduates and faculty to gain skills, relevant experience as well as learn from the implementation process. This paper presents lessons and experiences of the METEGA project, including institutional and operational issues that can be used to inform future academic mobility arrangements in Africa and elsewhere in the world.